Wiedza pielęgniarek pracujących w szpitalu na temat profilaktyki raka szyjki macicy jest niewystarczająca = Insuffitient knowledge about the profilaxy of cervial carcinoma among nurses working in the hospital - Kostrzewa-Zabłocka, Ewa; Dziemidok, Piotr; Makara-Studzińska, Marta (Journal of Education, Health and Sport, 2015)
Kostrzewa-Zabłocka Ewa, Dziemidok Piotr, Makara-Studzińska Marta. Wiedza pielęgniarek pracujących w szpitalu na temat profilaktyki raka szyjki macicy jest niewystarczająca = Insuffitient knowledge about the profilaxy of cervial carcinoma among nurses working in the hospital. Journal of Education, Health and Sport. 2015;5(4):229-244. ISSN 2391-8306. DOI: 10.5281/zenodo.16866 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A229-244 https://pbn.nauka.gov.pl/works/554864 http://dx.doi.org/10.5281/zenodo.16866 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 10.04.2015. WIEDZA PIELĘGNIAREK PRACUJĄCYCH W SZPITALU NA TEMAT PROFILAKTYKI RAKA SZYJKI MACICY JEST NIEWYSTARCZAJĄCA INSUFFITIENT KNOWLEDGE ABOUT THE PROFILAXY OF CERVIAL CARCINOMA AMONG NURSES WORKING IN THE HOSPITAL Ewa Kostrzewa-Zabłocka¹, Piotr Dziemidok¹, Marta Makara-Studzińska² ¹ Oddział Diabetologii, Instytut Medycyny Wsi im. Witolda Chodźki w Lublinie ² Zakład Psychologii Stosowanej Uniwersytet Medyczny w Lublinie dr n.med. Ewa Kostrzewa-Zabłocka 601-590-393 email: ewak@post.pl Nazwa jednostki: Oddział Diabetologii, Instytut Medycyny Wsi im. Witolda Chodźki w Lublinie/ Adres do korespondencji: ul. Lwowska 6/1 22-100 Chełm Streszczenie Wstęp: Od momentu odkrycia powiązań między wirusem HPV a rakiem szyjki macicy, dokonał się ogromny postęp w rozumieniu etiopatogenezy tej choroby. Szacuje się, że ok. 80% kobiet przynajmniej raz w życiu jest zakażonych tym wirusem nie wiedząc o infekcji. Chorobie można zapobiegać poprzez połączenie szczepienia przeciwko HPV i regularne wykonywanej cytologii. Cel: Sprawdzenie wiedzy pielęgniarek pracujących w szpitalu w zakresie profilaktyki raka szyjki macicy. Materiał i metody: Przebadano grupę 100 pielęgniarek z losowo wybranych oddziałów Samodzielnego Publicznego Szpitala Wojewódzkiego w Zamościu. Badanie przeprowadzono w dniach 23-27.09. 2013 roku. W pracy wykorzystano metodę sondażu diagnostycznego. Opracowano ankietę według obowiązujących norm i zasad konstruowania kwestionariusza badawczego, zawierała 28 pytań. Oprócz metryczki, problematyka zawarta w ankiecie wiedzy pielęgniarek pracujących w szpitalu w zakresie profilaktyki raka szyjki macicy. Wyniki: Z przeprowadzonych badań wynika, że badane pielęgniarki (71%) regularnie poddają się badaniom profilaktycznym, a ponad połowa badanych (67%) popiera inicjatywę szczepień przeciwko wirusowi brodawczaka ludzkiego. Z drugiej strony znaczy to, ze 1/3 fachowych pracowników służby zdrowia mających kontakt z pacjentami nie jest poddawana regularnym badaniom diagnostycznym i nie popiera koncepcji masowych szczepień przeciwko wirusowi brodawczaka ludzkiego. 87% pielęgniarek przyznaje, iż działania w szkołach, mediach, gabinetach lekarskich na płaszczyźnie uświadamiania kobiet o zagrożeniach, jakie niesie ze sobą rak szyjki macicy, są niewystarczające. Wniosek: W badanej grupie Program Wczesnego Wykrywania Raka Szyjki Macicy nie funkcjonuje w sposób prawidłowy. Słowa kluczowe: rak szyjki macicy, HPV, edukacja zdrowotna, wiedza personelu medycznego. Abstract Introduction: Since the discovery of links between HPV virus and cervical cancer, has made a huge progress as defined in etiopathogenesis of this disease. It is estimated that ok. 80% of women at least once in a lifetime is infected with this virus without knowing about the infection. The disease can be prevented through a combination of vaccination against HPV and regular cytology done. Objective: To verify the knowledge of nurses working in the hospital in the prevention of cervical cancer. Material and methods: We studied a group of 100 nurses from randomly selected branches of Public Provincial Hospital Alone in Zamość. The study was conducted on 23-27.09. 2013. In the work of the diagnostic survey method. The questionnaire was developed according to the standards and principles of the construction of the research questionnaire, contained 28 questions. In addition to the metrics, information contained in a survey of knowledge of nurses working in the hospital in the prevention of cervical cancer. Results: Studies show that tested nurses (71%) and regularly submit to prophylactic examinations, and more than half of the respondents (67%) supports the initiative of the vaccination against the human papilloma virus. On the other hand, this means that 1/3 of expert health professionals coming into contact with patients is not subjected to regular diagnostic tests, and does not endorse the concept of mass vaccination against the human papilloma virus. 87% of nurses acknowledges that action in schools, the media, the surgeries on the women’s awareness about the dangers posed by cervical cancer, are insufficient. Conclusion: in the test Group Program for early detection of cervical cancer is not functioning properly. Key words: cervical cancer, HPV, health education, knowledge of medical personnel.